DAMPAK KONSOLIDASI TERHADAP PROFITABILITAS PT SEMEN INDONESIA Tbk. (SMGR) - Deidrayanti Putri, Anhesa Rinta; Juniarti, Rina; Pangiarti, Endang Kartini (Transpublika Publisher, 2023)
A business combination is the merger of two or more separate companies into one entity with another company, enabling control over the operational activities. Consolidation is often employed as an alternative to expand and enlarge the business market, consequently impacting the company's profitability. This study aims to analyze the effect of company consolidation on profitability levels, utilizing financial ratios such as Return On Assets (ROA), Return On Equity (ROE), and Return On Investment (ROI) as indicators. It employs a quantitative approach, utilizing secondary data derived from the consolidated financial statements of Semen Indonesia Tbk. companies. The study compares account items and incorporates literature reviews focusing on financial performance data. The analysis reveals that prior to consolidation, PT Semen Baturaja Tbk. displayed an ROA level of 0.43%, ROE of 0.45%, and ROI of 0.27, all of which were below 1 (<1). However, after consolidation at PT Semen Baturaja Tbk., there was a noticeable increase in the company's ROA, ROE, and ROI, reaching 2.21%, 2.81%, and 1.82%, respectively.